2016
DOI: 10.1007/s11239-016-1360-5
|View full text |Cite
|
Sign up to set email alerts
|

The association between ABO blood group and obstetric hemorrhage

Abstract: descriptive, χ(2) (p < 0.05 significant) and multivariable regression models [odds ratio (OR), 95 % confidence interval (CI), p value]. 125,768 deliveries were included. After multivariable analysis, women with O blood type relative to women with non-O blood type had significantly higher odds of postpartum hemorrhage (OR 1.14; 95 % CI 1.05-1.23, p < 0.001), higher odds of statistically significant hemoglobin decreases of >2, 3, or 4 g/dL (OR 1.07; 95 % CI 1.04-1.11, p < 0.001, OR 1.08; 95 % CI 1.03-1.14, p = 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 19 publications
1
19
2
Order By: Relevance
“…Drukker et al found that a drop of haemoglobin by 20, 30 and 40 g/L after delivery was seen significantly more often in blood group O patients. 19 Further, the analysis of blood specimen which were taken 6-9 months after delivery from women enrolled in the "NOHA First cohort" revealed that low levels of VWF and blood group O carrier status were independently associated with a significant risk of severe PPH. 10 This supports our assumption that blood group O and along with it lower levels of active VWF constitutes a risk factor for increased postpartum blood loss.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drukker et al found that a drop of haemoglobin by 20, 30 and 40 g/L after delivery was seen significantly more often in blood group O patients. 19 Further, the analysis of blood specimen which were taken 6-9 months after delivery from women enrolled in the "NOHA First cohort" revealed that low levels of VWF and blood group O carrier status were independently associated with a significant risk of severe PPH. 10 This supports our assumption that blood group O and along with it lower levels of active VWF constitutes a risk factor for increased postpartum blood loss.…”
Section: Discussionmentioning
confidence: 99%
“…Our study findings are concordant with studies that have been published previously. Drukker et al found that a drop of haemoglobin by 20, 30 and 40 g/L after delivery was seen significantly more often in blood group O patients . Further, the analysis of blood specimen which were taken 6‐9 months after delivery from women enrolled in the “NOHA First cohort” revealed that low levels of VWF and blood group O carrier status were independently associated with a significant risk of severe PPH .…”
Section: Discussionmentioning
confidence: 99%
“…Early PPH is defined as bleeding that occurs within 24 hours from birth, while late PPH occurs between 24 hours and 6 weeks postpartum [3]. Identifying pre-delivery risk factors allows for earlier recognition and prevention of PPH [4]. Coagulation disorders are recognized as underlying causes for PPH, with von Willebrand disease (VWD) being the most common hereditary coagulopathy associated with PPH [5].…”
Section: Introductionmentioning
confidence: 99%
“…Though the difference in transfusion volume did not reach statistical significance, there was a tendency toward increased hemorrhage in type O patients. Similarly, increased risk of post‐partum hemorrhage with OR 1.14 ((95% CI 1.05–1.23); p < 0.001) has been observed in type O women in a retrospective study involving 125,768 deliveries, but again, no significant difference in blood product usage between O and non‐O type was found. Furthermore, a meta‐analysis from 2013, including 22 studies and 9,468 surgical and non‐surgical patients, reported an OR of 1.33 (95% CI 1.25–1.42); p < 0,001) for bleeding complication in patients with type O compared to non‐O.…”
Section: Discussionmentioning
confidence: 78%
“…Earlier studies on hemorrhage and transfusion in relation to blood type have been contradictory. A meta‐analysis of surgical and non‐surgical patients showed a significant increase in hemorrhage in patients with type O compared with non‐O, whereas there is contradictory results both for and against an increased need for transfusion in relation to surgery in patients with type O. Recently, an increased mortality due to trauma induced hemorrhage was reported in patients with type O .…”
mentioning
confidence: 99%